Podcasting in Serbia: Podcasters’ Perspectives on Emerging Roles, Practices, and Functions - Simona Žikić; Čedomir Markov (Media and Communication)
Podcasting has become increasingly popular in Serbia, a hybrid regime country characterized by profound polarization, a lack of media professionalism, and widespread anti-press sentiment. This study aimed to explore how podcast creators view their roles and practices within the evolving media landscape, as well as the implications of podcasting’s growing popularity in the Serbian public sphere. The data were obtained through focus groups with 16 independent and mainstream media-affiliated podcasters, exploring their perspectives on podcasting’s distinctiveness, functions, affordances, and obstacles. Participants noted the ability of podcasts to provide in-depth analysis of often neglected topics due to their flexible, informal presentation style, as opposed to the perceived routinization, rigidity, and superficiality of traditional media. Podcasters affiliated with professional media described podcasting as an extension of their practices, providing behind-the-scenes insights and additional journalistic content, whereas independent podcasters prioritized genuine conversations to create resonant content tailored to specialized communities. Journalist podcasters attributed the appeal of podcasting to the authenticity and intimacy it creates but emphasized the struggles of matching these features with journalistic standards. While most participants believed that podcasting contributes to greater external pluralism by providing a space for neglected subjects, alternative narratives, and marginalized voices, some were concerned about the possibility of exacerbating polarization, as podcasts frequently serve divided audiences. By exploring the perspectives Serbian podcasters bring to production and the meanings they attach to their roles and practices, this study offers insights for scholars and practitioners exploring media innovation in hybrid regimes and emerging democracies.